2019
DOI: 10.2147/ijn.s190354
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Effect of superparamagnetic nanoparticles coated with various electric charges on &alpha;-synuclein and &beta;-amyloid proteins fibrillation process</p>

Abstract: BackgroundMost of nanoparticles are nontoxic and have high absorption capability. Therefore, nanoparticles binding can effectively restrain fibrillation of β-amyloid and α-synuclein proteins and eventually prevent the toxicity of pathogenesis peptide of Alzheimer. Super paramagnetic iron oxide nanoparticles (SPIONs) contain iron oxide core which can be connected to a special part through magnetic coating.Materials and methodsIn this study, the effect of SPIONs with different charges was simultaneously examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Therefore, with the change of surface charge from positive to negative by some coatings, the level of protein aggregation or amyloid-fibrillation along with cytotoxicity can be greatly reduced. In this regard, Javdani, Rahpeyma, Ghasemi, Raheb43 exhibited that the change in the surface charge of iron NPs from positive to negative by dextran would reduce amyloid-fibrillation in both β-amyloids and α-syn.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, with the change of surface charge from positive to negative by some coatings, the level of protein aggregation or amyloid-fibrillation along with cytotoxicity can be greatly reduced. In this regard, Javdani, Rahpeyma, Ghasemi, Raheb43 exhibited that the change in the surface charge of iron NPs from positive to negative by dextran would reduce amyloid-fibrillation in both β-amyloids and α-syn.…”
Section: Discussionmentioning
confidence: 99%
“…By applying thioflavin-T fluorescence emission, the effect of SPIONs with different electric charges on both β-amyloid and α-synuclein fibrillation process was investigated. The negatively charged nanoparticles encoded to -COOH by dextran-coating decreased the binding level of thioflavin-T particles to β-sheets (Javdani et al, 2019).…”
Section: Application Of Iron Oxide Nanoparticles In the Treatment Of Admentioning
confidence: 98%
“…Some research groups have reported the use of NPs as a therapeutic approach to target amyloidosis. Recent data suggest that these nanomaterials can act as potential inhibitors of amyloid aggregation. Moreover, it was observed that NPs had the ability to affect amyloid formation owing to their surface properties. Surface-coated NPs were first developed to increase their bioactivity and biocompatibility.…”
Section: Introductionmentioning
confidence: 99%